Insomnia And Fertility Issues Among Women: A Review Study - Neha Vasisht; Dr. Sandeep Kumar Singh; Dr. Rudra Bhandari (Revista Electronica de Veterinaria, 2024)
Objective: This study expected to investigate that insomnia is determined by women’s health and wellbeing. Especially in terms of fertility. In today’s scenario sleep and insomnia can affects women physical, emotional, and psychological health and wellbeing later disturbs fertility among women. Then what would be the degree and what process. This review will show the relation between sleep, insomnia, and women’s fertility. The purpose of this review article should be to provide a valuable, authentic information, critical summary of a well-defined area. Method: We have searched published articles on Google Scholar, Willy, PubMed, Springer and Science Direct from 2000 to 2023 in English to investigate infertility, menstrual health, insomnia, and their effect on infertility. We have searched 6,820 articles. Total 46 papers were finalized. 33 from Google Scholar, 4 from PubMed, 6 from Science Direct, 1 from Springer and 1 from John Wiley. Result: This evaluation encompassed exclusively descriptive quantitative research that delineated various facets of sexuality within the framework of infertility. The findings indicated that infertility and associated treatment methods for fertilization may result in alterations to sexual self-esteem, sexual relationships, overall welfare, and sexual function. Conclusion: Insomnia may negatively impact woman’s fertility.